A dona da boca, a vendedora e a mula: o processo de criminalização de mulheres no tráfico de drogas em Santa Maria - RS - Melo, Andrey Régis de (2018)
The present research aims to analyze the process of criminalization of women in drug trafficking in Santa Maria - RS. With the enactment of Law 11,343 / 2016, it was possible to perceive a substantial growth of the female prison population. By 2016, data from the Ministry of Justice indicated that the majority of women prisoners were involved in drug trafficking. The understanding of the aforementioned process takes place from the revision of criminological theories and discourses such as anomia, the approaching approach and critical criminology, as well as the necessary discussion about gender problems, such as the politics of submission and correction of the woman that is associated with vulnerability provoked by the directing of the penal punitive system to the impoverished social classes. It is from the analysis of the criminal cases that were tried in the Court of Justice of the State of Rio Grande do Sul that the understanding about the behavior of the actors of the judicial field was sought and how the power-knowledge of the police approach contributes to the social construction of the woman as a drug trafficker to the detriment of criminal justice itself. Interviews with women accused of drug trafficking also authorize the understanding of the process of criminalization beyond the criminal-legal ritual of the courtroom and the case file, narratives on involvement with drug trafficking feature the crime fully expose the possibility of further interpretations for the criminal episodes that led women to sentencing and jail.